An ALMA survey of CO in submillimetre galaxies: companions, triggering, and the environment in blended sources. Issue 3 (14th June 2018) - Wardlow, J L; Simpson, J M; Smail, Ian; Swinbank, A M; Blain, A W; Brandt, W N; Chapman, S C; Chen, Chian-Chou; Cooke, E A; Dannerbauer, H; Gullberg, B; Hodge, J A; et al.
ABSTRACT: We present ALMA observations of the mid-J 12 CO emission from six single-dish selected 870-μm sources in the Extended Chandra Deep Field-South and UKIDSS Ultra-Deep Survey fields. These six single-dish submillimetre sources were selected based on previous ALMA continuum observations, which showed that each comprised a blend of emission from two or more individual submillimetre galaxies (SMGs), separated on 5–10 arcsec scales. The six single-dish submillimetre sources targeted correspond to a total of 14 individual SMGs, of which seven have previously measured robust optical/near-infrared spectroscopic redshifts, which were used to tune our ALMA observations. We detect CO(3–2) or CO(4–3) at z = 2.3–3.7 in 7 of the 14 SMGs, and in addition serendipitously detect line emission from three gas-rich companion galaxies, as well as identify four new 3.3 mm selected continuum sources in the six fields. Joint analysis of our CO spectroscopy and existing data suggests that 64(± 18) per cent of the SMGs in blended submillimetre sources are unlikely to be physically associated. However, three of the SMG fields (50 per cent) contain new, serendipitously detected CO-emitting (but submillimetre-faint) sources at similar redshifts to the 870 μm selected SMGs we targeted. These data suggest that the SMGs inhabit overdense regions, but that these are not sufficiently overdense on ∼100 kpc scales to influence the source blending given the short lifetimes of SMGs. We find that 21± 12 per cent of SMGs have spatially distinct and kinematically close companion galaxies (∼8–150 kpc and ≲ 300 km s −1 ), which may have enhanced their star formation via gravitational interactions.